THE RELATIONSHIP BETWEEN GENDER AND PERCEPTIONS OF HOUSEHOLD CHEMICALS: QUANTITATIVE STUDY AMONG HOUSEWIVES AND FATHERS - Solaeman Demih; Agustinus Indou; Lukas Saiba; Oman Sukmana; Tri Sulistyaningsih (SOSIOEDUKASI, 2025)
The daily life use of household chemicals is inevitable. Household products like household cleaning products, floor cleaners, disinfection water, rinsing water, and fabric bleach are more often used in the household operation. As attitudes toward chemical risks are the products of knowledge, experience, and cultural values of gender roles, they are quite subjective. It is worth mentioning also that this research has scientific urgency in an interdisciplinary context, especially in gender studies, public health and environmental psychology. This research uses a quantitative method as well as an analytical survey by discussing gender and feelings of household chemicals. This technique allows the researcher to gather and analyze data on a more scientific level in order to detect correlations between the variables. Based on the results of the quantitative analysis, it can be concluded that there is a positive and significant relationship between gender and the perception of household chemicals among housewives and fathers.